Qualitative comparison of link shaping techniques. (6th July 2010) - Chertov, R.; Almeroth, K.
Over the last several years there has been an ever increasing trend in using emulated testbeds for network experimentation. Emulated testbeds offer a reproducible and highly controlled experimental environment; however, due to the physical proximity of the nodes to each other in the data centre, the available links have very low propagation delays and unrealistic bandwidth. In this work, we conduct a qualitative comparison of three link shaping approaches. We focus on evaluating approaches as opposed to individual link shaping tools. Our goal in this work is to ascertain which approach yields the fewest emulation artefacts. Our results indicate that a transparent link shaping node significantly outperforms the other two methods.